Impact of exercise training on physiological measures of physical fitness in the elderly - Mendonca, G. V. (2016)
BACKGROUND: Older persons are the fastest growing segment of the population living in the Western hemisphere. Longevity comes at a price, including a higher rate of morbidity, functional and mental disability and the eventual loss of independence. Physical inactivity further aggravates the decline in physiological function along the aging process. Therefore, the promotion of regular exercise may be seen as one of the main non-pharmacological approaches that should be recommended to older adults. METHODS: We performed a comprehensive review on the interaction between exercise training and improved physical fitness in the elderly. Specifically, 175 papers describing the overall benefits of exercise training on the cardiovascular, neuromuscular and brain function of older adults were included. The effectiveness of training for improving quality of life at an older age was also reviewed. RESULTS: Exercise training can partially reverse the age-related physiological decline and enhance work capacity in the elderly. Numerous studies have shown that maintaining a minimum quantity and quality of physical exercise decreases the risk of cardiovascular mortality, sarcopenia, prevents the onset of osteopenia and even exerts a prophylactic role against neurodegeneration. The systemic physiologic effects are profound and may be directly linked to a favorable feedforward cycle whereby improved physiologic function begets improved physical function and so on. CONCLUSION: We conclude that structured training programs should be designed to improve the physiological function in this population. Finally, the benefits of exercise training vary as a function of training volume and this relationship is independent of age and sex.